Kajian Prioritas Pembangunan Prasarana Jalan Pedesaan Berdasarkan Rural Access Index (RAI) di Kawasan Agropolitan Ciwidey Kabupaten Bandung - Dewandaru, Dimas Sigit (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
In 2006, the World Bank introduced a method of assessment of accessibility to an rural area known as the Rural Access Index (RAI). According to the definition of the World Bank, RAI is a method of measuring accessibility of rural people who live in the area of two kilometers (usually equivalent to walking 20-25 minutes) from the road to pass a vehicle in all-season as a proportion of the total rural population. The low RAI index indicates that area is in dire need of access roads. RAI calculation methods stressed for accessibility and population, so this approach is more appropriate when used to determine the priorities list of rural access road in Agropolitan Area. This study aimed to assess the method of determining the priority list of rural road infrastructure development through the Rural Access Index calculation. RAI calculations performed for all villages in Ciwidey Agropolitan Area. The village with the lowest RAI value will be included in the priority list of road construction programed. The selected road priority that will be constructed conducted economic analysis to prove the feasibility of the construction project. The results of this study indicate that the prioritization of rural roads in the area Ciwidey Agropolitan Area can be accomplished by using the RAI. The selection’s roads that resulted using RAI methods can also be taken into consideration in decision-making and programming rural road construction by local governments. This is evidenced from the Economic Feasibility analysis which showed positive results, meaning that the project on the priority road is feasible.